Determinants and Consequences of Disruptive Innovations: Evidence from The UK Financial Services Sector - Tasawar Nawaz (Journal of Accounting and Management Information Systems (JAMIS), 2018)
Building on the assumption that intangible and tangible corporate resources are indispensable to create and sustain firm value in today's knowledge-driven economy; this paper empirically examines the determinants and consequences of disruptive innovations in the context of the UK financial services sector. The major contribution of this paper is to provide novel insights into the value creation process in one of the world's leading financial services sector. In doing so, the paper exploits various properties of the selected financial institutions and submits that financial and human capital resources drive value in the UK's financial services sector. The paper makes informed suggestions for the financial institutions operating in the UK and abroad. The results observed in the present study will potentially enhance the understanding of the international audiences on the banking business model practiced by the UK-based financial institutions.
Keywords: C12; G15; G20; G21; G24; 650; disruptive innovations; corporate resources; intellectual capital-based view; firm value; UK Financial services sector; Brexit